Do men and women economists choose the same research fields? Evidence from top 50 departments - Dolado, Juan J. 1955-; Felgueroso, Florentino; Almunia, Miguel (Discussion paper series / Centre for Economic Policy Research, 2006)
This paper describes the gender distribution of research fields chosen by the faculty members in the top 50 Economics departments, according to the rankings available on the Econphd.net website. We document that women are unevenly distributed across fields and test some behavioural implications from theories underlying such disparities. Our main findings are that the probability that a woman chooses a given field is positively related to the share of women in that field (path-dependence), and that the share of women in a field at a given department increases with the sizes of the department and field, while it decreases with their average quality. However, these patterns seem to be changing for younger female faculty members. Further, by using Ph.D. cohorts, we document how gender segregation across fields has evolved over the last four decades.